Development of Hanzi Radical Learning Media 女字旁 (nǚ zì páng) for Students of the Chinese Language Education Program at State University of Semarang - Putri, Shinta Meiviana Harindra; Pamuji, Dian Yuni; Agwinanda, Almira (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to develop an innovative learning medium in the form of a pull the tab pop-up book focusing on the understanding of the hanzi radical 女 (nǚ zì páng) for students of the Chinese Language Education Program at Universitas Negeri Semarang. The research is motivated by students difficulties in memorizing and understanding the complex structure and meaning of hanzi. The methodology questionnaires, product design, expert validation, and revision stages. The resulting product is printed on ivory paper with attractive colored visuals, organizing hanzi characters by stroke count, complete with pinyin and translations. Validation results from media and content experts indicate the media is suitable as a learning aid. The validation results of the instructional media by the subject matter expert obtained an average score of 87,4, which falls within score level 4, indicating it is highly appropriate. Meanwhile, validation by the media expert yielded an average score of 86,8 also classified within score level 4, suggesting the media is highly suitable for use. These results were accompanied by improvement suggestions to enhance the quality and effectiveness of the media’s utilization.